A new classification of inferior alveolar nerve repositioning procedure for dental implants placement presentation and illustrative cases. (October 2021) - Kablan, F.
Abstract : Objectives: Tooth loss is one of the most common causes of reduced quality of life in adults. Recently there is an increasing global interest in treatments involving the Inferior Alveolar Nerve (IAN) repositioning for dental placement but standardization and classification of the techniques is warranted. In the present paper, a new classification is suggested, illustrated, and discussed. Patients and Methods: A retrospective analysis of the preoperative radiographic records and the documents of the surgical procedures during a ten year period between 2008 -2018 of patients who had been treated with implant placement in conjunction with IAN repositioning of posterior atrophic mandible was performed. The cases were categorized according to the available bone, the nerve location, and the surgical intervention into four groups. Results: Overall, 132 edentulous posterior mandibles in 98 patients (72 women, 26 men; age range 20-75 years) were included in the analysis. Those sites were divided into four categories: Category 1, included 54 patients with 72 sites, and was treated by one surgery. Category 2; included 15 patients with 15 sites and was treated with two stages. Category 3, included 17 patients with 21 sites, and category 4, included 12 patients with 24 sites. The treated 132 sites with IAN repositioning received 379 dental implants. All the sites were restored by an implant-supported fixed prosthesis. The patients reported good function and improvement in their quality of life. Conclusions: This new classification might enhance diagnosis and help predict the treatment stages of the patients requiring IAN repositioning for dental implant placement.